Differentiation and histogenesis of syringomatous tumour of the nipple and low‐grade adenosquamous carcinoma: evidence for a common origin. Issue 1 (9th April 2014) - Boecker, Werner; Stenman, Göran; Loening, Thomas; Andersson, Mattias K; Sinn, Hans‐Peter; Barth, Peter; Oberhellmann, Felix; Bos, Inge; Berg, Tobias; Marusic, Zlatko; Samoilova, Vera; Buchwalow, Igor
<x xml:space="preserve">Abstract</x> Aims Syringomatous tumour of the nipple and low‐grade adenosquamous carcinoma (LGAdSC) of the breast are regarded as distinct entities. To clarify the nature of these two lesions, we compared the expression of different lineage/differentiation markers in 12 syringomatous tumours of the nipple, nine LGAdSCs, and normal breast epithelium. Methods and results Using triple immunofluorescence labelling and quantitative RT‐PCR for keratins, p63, and smooth muscle actin, we demonstrated that syringomatous tumour and LGAdSC contain p63+/K5/14+ tumour cells, K10+ squamous cells, and K8/18+ glandular cells, with intermediary cells being found in both lineages. Identical p63+/K5/14+ cells were also found in the normal breast duct epithelium. Conclusions Our data provide evidence that syringomatous tumour of the nipple and LGAdSC are identical or nearly identical lesions. They contain p63+/K5/14+ cells as the key cells from which the K10+ squamous lineage and the K8/18+ glandular lineage arise. On the basis of our findings in normal breast tissue and associated benign lesions, we suggest that p63+/K5/14+ cells of the normal breast duct epithelium or early related cells might play a key role in the neoplastic transformation of both syringomatous tumour and LGAdSC. We propose that the differentiation patterns found in both lesions reflect the early ontogenetic stages of the normal breast epithelium.